2009
DOI: 10.1007/s10286-009-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response in primary Raynaud’s phenomenon

Abstract: Dysregulation of cholinergic sympathetic fibres innervating the fingers was found in PRP. Abnormal peripheral mechanisms may be the cause. Since SSR habituation was also not normal, even central mechanisms may be implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Mondelli et al [ 34 ] found that the latency of SSR was prolonged in patients with primary Raynaud's phenomenon. Uncini et al [ 6 ] reported that the SSR amplitude varied between people and that several factors influence the SSR amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Mondelli et al [ 34 ] found that the latency of SSR was prolonged in patients with primary Raynaud's phenomenon. Uncini et al [ 6 ] reported that the SSR amplitude varied between people and that several factors influence the SSR amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies did not consider the amplitude as a valid measure of normality versus abnormality. 20,27 Also, there was no relationship between the type of SSR abnormality and intensity of autonomic impairment. In one study, in reflex sympathetic dystrophy, the mean amplitude and onset latency of SSR in the involved limb was greater and shorter than that the uninvolved limb.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, they did not measure the SSR amplitude; they measured the area because it had a good accuracy of total sympathetic excitability of the nerve. 20 According to a study carried out by Charkoudian, the sympathetic nervous system, via both peripheral (local) and central system mechanisms, plays a critical role in the pathogenesis of primary and secondary RP. 21 Pancera et al investigated the sympathetic hyperactivity in systemic sclerosis and PRP.…”
Section: Discussionmentioning
confidence: 99%
“…22 Mondelli et al evaluated the SSR in primary Raynaud’s phenomenon and found that the latency of SSR was prolonged in patients with primary Raynaud’s phenomenon. 23 …”
Section: Discussionmentioning
confidence: 99%